Life and belief in the experience of John W. Laing, CBE - Harrison, Godfrey (London, UK Hodder and Stoughton, 1954)
Includes photographs.
Signed by subject. Brethren writer.
Keywords: Laing, John W. -- 1879-; Brethren movement -- biography